Searching for general model of conspiracy theories and its implication for public health policy: Analysis of the impacts of political, psychological, structural factors on conspiracy beliefs about the covid-19 pandemic - Kim, Seoyong; Kim, Sunhee (International Journal of Environmental Research and Public Health, 2021)
Along with the spread of the COVID-19 pandemic, beliefs in conspiracy theories are spreading within and across countries. This study aims to analyze predictors of beliefs in conspiracy theories. Because previous studies have emphasized only specific political, psychological, or structural factors or variables, this study constructs an integrated analytical model that includes all three factors. We analyze data from a large-scale survey of Koreans (N = 1525) and find several results. First, political, psychological, and structural factors influence beliefs in conspiracy theories. Second, when we examine the specific influences of the variables, we find that authoritarianism, support for minority parties, religiosity, trust in SNS (social networking services), perceived risk, anxiety, negative emotions, blame attribution, the quantity of information, health status, and health after COVID-19, all positively influence beliefs in conspiracy theories. Conversely, support for President Moon Jae-In’s government, Christianity, trust in the government, perceived control, analytic thinking, knowledge, the quality of information, and gender, all negatively impact these beliefs. Among the predictors, the quality of information, health status, support for President Moon Jae-In’s government, perceived risk, and anxiety have the most decisive impacts on beliefs in conspiracy theories.
Keywords: COVID-19; Health Knowledge, Attitudes, Practice; Health Policy; Humans; Pandemics; Politics; Public Opinion; Republic of Korea; Belief in conspiracy theories; Conspiracy theory; COVID-19 pandemic; General model of conspiracy theories; Social construction of conspiracy theory